Effect of UVA radiation on the Nrf2 signalling pathway in human skin cells - Ryšavá, Alena; Čížková, Kateřina; Franková, Jana; Roubalová, Lenka; Ulrichová, Jitka; Vostálová, Jitka; Vrba, Jiří; Zálešák, Bohumil; Rajnochová Svobodová, Alena (Journal of photochemistry and photobiology. B, Biology, 2020)
The harmful effects of low energy UVA photons (315-400 nm) are associated with the massive production of reactive oxygen species resulting in oxidative stress. In response to oxidative damage, NF-E2-related factor 2 (Nrf2) is translocated to the nucleus and drives the expression of detoxication and antioxidant enzymes. UVA's effect on Nrf2 has been quite well characterised in dermal fibroblasts. However, there is a dearth of such information for keratinocytes. This study aimed to evaluate and compare the effect of UVA radiation on the Nrf2 pathway and oxidative stress related proteins in primary human dermal fibroblasts (NHDF), epidermal keratinocytes (NHEK) and human keratinocyte cell line HaCaT. NHDF were exposed to doses of 2.5-7.5 J/cm2, NHEK and HaCaT to 10-20 J/cm2 using a solar simulator. Effects on Nrf2 translocation were evaluated after 1, 3 and 6 h and Nrf2-controlled proteins (heme oxygenase 1 (HO-1), NAD(P)H:quinone oxidoreductase 1 (NQO1), glutathione reductase (GSR), glutathione-S-transferase (GST), interleukine-6 (IL-6), and matrix metalloproteinases (MMP-1, MMP-2)) after 3, 6 and 24 h. The results showed the fastest Nrf2 translocation was in UVA-irradiated HaCaT (1 h), persisting until the subsequent time interval (3 h), while in primary keratinocytes the effect of radiation was minimal. In NHDF, UVA-stimulated Nrf2 translocation was conspicuous 3 h after UVA treatment. In NHDF, most of the studied proteins (NQO1, HO-1, GSR, GSTM1 and MMP-1) showed the highest level 24 h after UVA exposure, except for MMP-2 and IL-6 which had their highest level at a shorter time incubation interval (3 h). In NHEK, NQO1, HO-1 and GST were increased 6 h after UVA exposure, GSR and MMP-2 level was slightly below or above the control level, and MMP-1 and IL-6 increased at shorter time intervals. When comparing NHEK and HaCaT, these cells displayed contrary responses in most of the Nrf2-controlled proteins. Thus, primary keratinocytes cannot be replaced with HaCaT when studying cell signalling such as the Nrf2 driven pathway and Nrf2-controlled proteins.
Keywords: viabilita buněk; faktor 2 související s NF-E2; Fibroblasts; NF-E2-Related Factor 2; Nrf2 pathway; signální transdukce; Cell Survival; kůže; Keratinocytes; Signal Transduction; ultrafialové záření; kultivované buňky; UVA radiation; keratinocyty; lidé; Skin; Humans; HaCaT; Primary skin cells; Ultraviolet Rays; Protein Transport; Cells, Cultured; transport proteinů